Os multiletramentos para a desencapsulação curricular no contexto do Projeto Digit-M-Ed 2017 - Barrozo, Luila (2019)
This research aims at critically understanding how Multiliteracies enable curricular de-encapsulation in a curriculum project developed by a research group for a university extension project aimed at school communities which included elementary to undergraduate students. This study is based on the Cultural-Historical Activity Theory and the Pedagogy of Multiletracies. The analyzed data were produced in an Extension Program called Digit-M-Ed Hiperconectando Brasil: transforming teaching and learning, a teacher education Project at the Pontifical Catholic University of São Paulo. The data selection was based on a theoretical framework which builds on Multiliteracies and curricular de-encapsulation. For this research, the guiding question was: How do Multiliteracies contribute to curricular de-encapsulation? This question was answered based on the main concepts that make up Multiliteracies: multimedia, multiculturality and multimodality; situated practice, overt instruction, critical framing and transformed practice. This study was organized within the Critical Collaborative Research framework, which aims at the intentional transformation of the subject in society. Meetings were organized weekly with the participants of the Language in Activities in the School Contexts Research Group, and monthly with teachers, researchers, principals, coordinators and students - all in the role of peer-educators - from public and private schools. The data were collected by video recordings of the meetings with the schools during the first semester of 2017. The analysis drew from the thematic content and the context of production and the observed lexical choices. The interpretation was based on the central concepts of Multiliteracies, based on the narrative of the activities carried out in the first semester of 2017. The results suggest that, in the critical collaborative process, Multiliteracies allow for the creation of a de-encapsulated curriculum, besides the construction and sharing of new knowledge by deconstructing crystallized practices